The comparison of morbid obesity quality of life and body image between surgery and other treatments: A case-control study - Negar Yazdani; Nasrin Elahi; Farkhondeh Sharif; Seyed Vahid Hosseini; Abbas Ebadi (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Morbid obesity is rising around the world. Surgery is a selective treatment intervention for it. Since most of the surgeons use weight loss for evaluating of the morbid obesity surgical outcomes and paying attention to the the quality of life (QOL) and body image evaluation are rare, this study aimed to assess the QOL and body image in pre- and postsurgery with other interventions. MATERIALSs AND METHODS: This case-control study was done on 200 morbidly obese patients (n = 100 in each group) who referred to the obesity clinic in Shiraz. The data were collected by Body Image Concern Inventory and 12-item Short Form Survey. The data were analyzed by t-test, Pearson correlation coefficient test, analysis of variance, and regression analysis. P = 0.05 was considered as significant. RESULTS: The paired t-test showed a significant difference in mean scores of body image (P < 0.001) and all dimensions of the QOL (P < 0.001) in the case and control groups. In the case group, there was a significant difference between the mean scores of the QOL and the different categories of body mass index (BMI) in postsurgery (P < 0.05) and the different mean scores of body image and the different categories of BMI in pre- and postsurgery wasn't significant (P > 0.05). Age was a predictor variable for the QOL of morbidly obese persons after surgery (P < 0.001). After surgery, men showed better QOL than women (P < 0.001). CONCLUSION: Final results indicated that body image and QOL defects caused by obesity could be more improvement after surgery. This study can promote health-care team's knowledge about holistic supporting of all dimensions' QOL of obese individuals. It is suggested that supporting interventions should be done as effective methods of maintenance for effects of weight loss methods such as surgery.